The Pengaruh Umpan Balik Guru Terhadap Kemampuan Menulis Siswa - Renata, Dina; Renati, Dini; Hidayah, Nurul; Indriani, Lilia (Universitas Nusantara PGRI Kediri, 2024)
Teacher feedback on students' essay writing is often an alternative for teachers to support the improvement of students' writing quality. This study has the main objective to find out the relationship between teacher’s feedback and student essay writing by looking at the difference in student essay scores before and after feedback. Methodology used in this research is descriptive quantitative by looking at the data of students' project scores in one class. The results showed that there was a good improvement in students' ability to write essays, this was shown through the average student score which had a significant difference between before and after being given feedback from the lecturer. The conclusion obtained through this research is that feedback from teachers is effective in improving the quality of student writing, especially in this research essay writing.